(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Teaching surgical skills effectively continues to be a significant hurdle in medical education. At the University Medical Center Hamburg-Eppendorf, the student-driven simulation laboratory, SimLab – Students for Surgery, enhances traditional teaching methods by offering a educational platform that not only aids students in basic surgical skills to improve transitioning to internships and medical residency but also incorporates 3D printing to simulate surgical scenarios more realistic like fractures, appendectomies and congenital anomalies. This integration aims to refine the extracurricular teaching and preoperative training through clinical collaborations. This study aims to assess the efficacy and impact of the SimLab approach, designed models and curricula on surgical education and student motivation for surgical careers, as well as its clinical utility, to provide insights for the development of additional simulation laboratories. SimLab facilitates diverse training modules ranging from basic laparoscopy to advanced surgical simulations, employing peer teaching, 3D printing, and digital reconstructions. Models are crafted from existing CT imagery or designed with open-source software, incorporating feedback from clinical partners into every prototype. Evaluations utilize student feedback through surveys and objective measures such as procedure time, execution speed, knot integrity, and eye-tracking during training sessions. Over 150 students have engaged with SimLab training, showing marked improvements in surgical competencies and reporting high satisfaction with the feasibility and educational quality of the simulations. Clinical integration of preoperative prints has notably enhanced preoperative planning and patient consultations. SimLab offers an ethically and cost-effective approach to surgical training, potentially increasing the safety and efficacy of surgical interventions and thereby hopefully benefiting patient care in the long-term.